Preclinical evaluation of a novel CEA‐targeting near‐infrared fluorescent tracer delineating colorectal and pancreatic tumors. Issue 8 (22nd June 2015) - Boonstra, Martin C.; Tolner, Berend; Schaafsma, Boudewijn E.; Boogerd, Leonora S.F.; Prevoo, Hendrica A.J.M; Bhavsar, Guarav; Kuppen, Peter J.K.; Sier, Cornelis F.M.; Bonsing, Bert A.; Frangioni, John V.; van de Velde, Cornelis J.H.; Chester, Kerry A.; et al.
<x xml:space="preserve">Abstract</x> Surgery is the cornerstone of oncologic therapy with curative intent. However, identification of tumor cells in the resection margins is difficult, resulting in nonradical resections, increased cancer recurrence and subsequent decreased patient survival. Novel imaging techniques that aid in demarcating tumor margins during surgery are needed. Overexpression of carcinoembryonic antigen (CEA) is found in the majority of gastrointestinal carcinomas, including colorectal and pancreas. We developed ssSM3E/800CW, a novel CEA‐targeted near‐infrared fluorescent (NIRF) tracer, based on a disulfide‐stabilized single‐chain antibody fragment (ssScFv), to visualize colorectal and pancreatic tumors in a clinically translatable setting. The applicability of the tracer was tested for cell and tissue binding characteristics and dosing using immunohistochemistry, flow cytometry, cell‐based plate assays and orthotopic colorectal (HT‐29, well differentiated) and pancreatic (BXPC‐3, poorly differentiated) xenogeneic human–mouse models. NIRF signals were visualized using the clinically compatible FLARE™ imaging system. Calculated clinically relevant doses of ssSM3E/800CW selectively accumulated in colorectal and pancreatic tumors/cells, with highest tumor‐to‐background ratios of 5.1 ± 0.6 at 72 hr postinjection, which proved suitable for intraoperative detection and delineation of tumor boarders and small (residual) tumor nodules in mice, between 8 and 96 hr postinjection. Ex vivo fluorescence imaging and pathologic examination confirmed tumor specificity and the distribution of the tracer. Our results indicate that ssSM3E/800CW shows promise as a diagnostic tool to recognize colorectal and pancreatic cancers for fluorescent‐guided surgery applications. If successfully translated clinically, this tracer could help improve the completeness of surgery and thus survival.